KEMAMPUAN BERADAPTASI MAHASISWA PERANTAU: APAKAH GAYA HIDUP HEDONIS DAN CULTURE SHOCK MEMILIKI PERAN? - Ferdianti, Restia; Sujadi, Eko; Putra, Betaria (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
Students studying outside their region often encounter challenges in their initial years of adaptation. This study investigates the impact of hedonic lifestyle and culture shock on the adjustment of the newcomer students. Employing a quantitative survey approach, data were gathered from newcomer students at a university in Jambi Province, Indonesia, utilizing convenience sampling, resulting in a sample of 93 students. The researchers utilized the Hedonic Lifestyle Scale, Culture Shock Scale, and Academic Adjustment Scale. Hypothesis testing utilized simple and multiple regression analyses. The research findings confirmed a significant negative correlation between hedonic lifestyle, culture shock, and the adaptation of international students, suggesting that lower hedonic lifestyle and culture shock correspond to higher adaptability levels. This study offers crucial insights for interventions targeting overseas students, focusing on mitigating hedonic lifestyle influences and alleviating culture shock